Fault tolerant emergency control to preserve power system stability. (August 2016) - Pedersen, Andreas S.; Richter, Jan H.; Tabatabaeipour, Mojtaba; Jóhannsson, Hjörtur; Blanke, Mogens
Abstract: This paper introduces a method for fault-masking and system reconfiguration in power transmission systems. The paper demonstrates how faults are handled by reconfiguring remaining controls through utilisation of wide-area measurement in real time. It is shown how reconfiguration can be obtained using a virtual actuator concept, which covers Lure-type systems. The paper shows the steps needed to calculate a virtual actuator, which relies on the solution of a linear matrix inequality. The solution is shown to work with existing controls by adding a compensation signal. Simulation results of a benchmark system show ability of the reconfiguration to maintain stability. Abstract : Highlights: This paper introduces a method for fault-masking and system reconfiguration in power transmission systems. The reconfiguration is obtained using a virtual actuator concept, which covers Lure type systems. The reconfiguration guarantees stability, locally recovers performance and has a wide-area communication delay compensation. The reconfiguration relies on the solution of a linear matrix inequality.